An EIRP Measurement Method of High-Power Microwave Systems Based on Near-Field Testing - Xianggang Hu; Jiancang Su; Mingtao Zhang; Xi Li; Dingkun Ma; Jingang Gong; Kewei Cheng; Jia Liu; Jiande Zhang; Rui Li; Jie Cheng; Shaotong Wu (International Journal of Antennas and Propagation)
The equivalent isotropic radiated power (EIRP) of high-power microwave (HPM) systems is a core-evaluating indicator. In practical testing, locating a suitable test site for the far-field method becomes challenging due to the requisite antenna separation. The conventional near-field method necessitates the extraction of the antenna’s near-field distribution, resulting in a testing system of intricate complexity and diminished efficiency. Therefore, the traditional near-field method cannot be directly applied in HPM systems. In the present study, a new EIRP measurement method for HPM systems based on near-field testing was proposed. First, a monitoring antenna of a considerable scale is positioned within the near-field vicinity of the HPM antenna to capture radiation power, thereby deriving its equivalent input power. Subsequently, according to the EIRP definition and the measured gain of the HPM antenna, the EIRP of the HPM system can be acquired. Theoretical research on this measurement method was conducted, the electromagnetic simulation model was constructed, and a comprehensive analysis through simulation was undertaken. A measurement system was developed and verified experimentally. The results demonstrate the precision of this approach in determining the EIRP of the HPM system, thereby serving as a valuable tool for assessing the power-handling capability of the HPM antenna. The test error is ±0.5 dB.